How to Weaken the EU Frame - Vattimo, Gianni; Zabala, Santiago (Identities: Journal for Politics, Gender and Culture, 2015)
Even though the European Union was created to avoid new wars within the continent and promote social integration, it has never questioned its political horizon. This is why legal scholars are continuously reminding us that until our constitution is ratified, the Union will continue to lack the political debate that is at the center of any mature democracy. But if the Union has now reached a new record of unpopularity it is because of this general neutering of politics, which allows technocrats to prevail over politicians and indifference over democracy. The logic behind our thesis is not that countries cannot leave the Union but that doing so would create more harm than staying. However, this does not imply there is no alternative; quite the contrary, a profound resistance to the Union has not only been discussed but also practiced throughout Europe. Author(s): Gianni Vattimo and Santiago Zabala Title (English): How to Weaken the EU Frame Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 81-83 Page Count: 3 Citation (English): Gianni Vattimo and Santiago Zabala, “How to Weaken the EU Frame,” Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 81-83.